A Hybrid Assembly of MXene with NH2−Si Nanoparticles Boosting Lithium Storage Performance. Issue 8 (23rd March 2020) - Cui, Yu; Wang, Jie; Wang, Xin; Qin, Jinwen; Cao, Minhua
Abstract: A facile hybrid assembly between Ti3 C2 Tx MXene nanosheets and (3‐aminopropyl) triethoxylsilane‐modified Si nanoparticles (NH2 −Si NPs) was developed to construct multilayer stacking of Ti3 C2 Tx nanosheets with NH2 −Si NPs assembling together (NH2 −Si/Ti3 C2 Tx ). NH2 −Si/Ti3 C2 Tx exhibits a significantly enhanced lithium storage performance compared to pristine Si, which is attributed to the robust crosslinking architecture and considerably improved electrical conductivity as well as shorter Li + diffusion pathways. The optimized NH2 −Si/Ti3 C2 Tx anode with Ti3 C2 Tx : NH2 −Si mass ratio of 4 : 1 displays an enhanced capacity (864 mAh g −1 at 0.1 C) with robust capacity retention, which is significantly higher than those of NH2 −Si NPs and Ti3 C2 Tx anodes. Furthermore, this work demonstrates the important effect of the MXene‐based electrode architecture on the electrochemical performance and can guide future work on designing high‐performance Si/MXene hybrids for energy storage applications. Abstract : A hybrid assembly of NH2 −Si/Ti3 C2 Tx, synthesized by drip adding positively charged NH2 −Si NPs into Ti3 C2 Tx methanol dispersion, exhibits an enhanced capacity (864 mAh g −1 at 0.1 C) with robust capacity retention.